A life course framework for understanding digital technology use in the transition to adulthood. (March 2021) - Mollborn, Stefanie; Fomby, Paula; Goode, Joshua A.; Modile, Adenife
Highlights: Applying a life course lens improves understanding of young adults' technology use. Teen technology use, current school enrollment, and peers predict technology time. Parenting practices shape young adults' emotions, future plans about technology use. Young adult technology use is highly malleable and weakly predicted by teen factors. Abstract: Rapid increases in young people's time spent using digital technology ("screen time") in the mobile internet era have led to anxiety about long-term effects. This mixed-method US study examines childhood experiences and contextual factors that shape screen time in the transition to adulthood. We recursively analyzed 56 qualitative interviews with young adults in a large metropolitan area in 2016–2018 and prospective longitudinal nationally representative survey data (PSID-CDS-2007 and PSID-TAS-2017) to articulate a conceptual framework of life course influences on young adults' time spent using digital technologies. Inductive qualitative analyses built an initial framework, which was assessed with quantitative data, then further refined with qualitative analyses. Young adults drew on life course perspectives when discussing influences on their current digital technology use. As they suggested, in quantitative analyses more frequent adolescent technology use and greater device access weakly predicted increased technology frequency. Current school enrollment and several current peer factors predicted technology time. Interviewees emphasized the influence of parenting around technology use during adolescence, but parenting did not predict young adult screen time in quantitative analyses. Further qualitative analyses suggested that instead of influencing current technology time, earlier parenting shaped current emotional responses and imagined future technology use. We found young adults' technology use frequency to be informed by earlier experiences but highly malleable. Past technology use and current social contexts matter, but only up to a point. Moving beyond time use to incorporate emotional responses and future plans can better capture how the life course shapes technology use.